Reflexões sobre a aprendizagem de Geometria nos anos finais do ensino fundamental com base no modelo de Van Hiele - Cruz, Andreza Oliveira (Universidade Federal do Tocantins, 2021)
The theme of this work seeks to investigate the teaching and learning process of geometry in elementary school based on the contributions of the Van Hiele model. This research was developed through a systematic review, in which we analyzed studies that sought to identify which of the five levels of geometric thinking in the Van Hiele model are and remain the students. These researches took as a reference the teaching of contents such as Polygons, Quadrilaterals and Polyhedron. The choice of this theme came about through experiences during the Supervised Internships where we noticed that the students had great difficulties in learning geometry. The research question is thus defined: How does Van Hiele's model, based on its levels, contribute to the development of geometric thinking in elementary schoolstudents? Our goal is to investigate the level of understanding of geometric thinking ofelementary school students in research that adopted the Van Hiele model. The results of the analyzed researches revealed that the Van Hiele model can be used for the teaching of geometryin Basic Education and that through his contributions the teacher assesses how the developmentof the students' geometric thinking is taking place in their classes.